EFFECT OF CORPUS LUTEUM AND STATUS OF ANIMAL ON RECOVERY RATE OF OOCYTES IN OVINE - SOFI, K A; KHAN, M Z; lslam, R; LONE, F A (The Indian Journal of Animal Reproduction, 2010)
Genital organs of slaughtered ewes were collected from abattoirs in Srinagar city and transported to the laboratory in warm normal saline solution containing 50μg gentamicin sulphate per ml. Upon arrival to the laboratory; the status of the reproductive tract (gravid or non-gravid) and ovaries for corpus luteum with or without were observed and recorded. The oocytes were collected separately from ovaries of gravid and non-gravid uteri as well as from ovaries with or without corpus luteum (CL) using slicing method and graded as good, fair and poor for each ovary under stereo-zoom microscope. The good quality, usable and total oocytes harvested from ovaries without CL were significantly (p <0.05) higher (3.13, 4.91 and 6.57) than the ovaries containing CL (2.55, 4.14 and 5.62). However, the number of good quality, usable and total oocytes recovered was non-significantly (p >0.05) higher for ovaries of non-gravid uteri (3.14, 4.92 and 6.45) than for ovaries of gravid uterus (1.96, 3.38 and 5.04 ). In conclusion, ovaries without CL were better for oocyte collection from abattoir ovaries in ovine.